Studi Literatur: Kemampuan Berpikir Kritis Matematis Melalui Model Pembelajaran Preprospec Berbantuan Scratch Bernuansa STEM - Sandika, Bagus; Dewi, Nuriana Rachmani (Papanda, 2026)
The critical mathematical thinking skills of students in Indonesia are still very low. This is due to the learning process which only emphasizes conceptual understanding. This study aims to examine students’ mathematical critical thinking skills through the implementation of the Preprospec learning model assisted by Scratch with a STEM approach, based on findings from previous studies. The research employed a literature review method by analyzing relevant national and international journal articles related to the ICT-assisted Preprospec model, Scratch media, STEM approach, and mathematical critical thinking skills. The data used is secondary data from relevant previous research and was obtained through searches on Google Scholar. The analysis techniques used include content analysis and secondary analysis. The results indicate that the ICT-assisted Preprospec learning model consistently enhances students’ active participation and depth of thinking through Problem Solving and Evaluation stages. The use of Scratch has been shown to increase learning motivation and engagement, while the STEM approach effectively connects mathematical concepts to real-world contexts. The integration of these components contributes significantly to the improvement of students’ mathematical critical thinking skills, particularly in analyzing problems, evaluating solution strategies, and drawing logical conclusions.